Hubungan Pola Asuh Orangtua dan Komunikasi Interpersonal Dengan Interaksi Sosial Remaja Karang Taruna Grogol RW 07 Blotongan Salatiga - Nita Heri Novia; Tritjahjo Danny S; Yari Dwikurnaningsih (Peneliti.net, 2023)
This research was conducted at Karang Taruna Grogol RW 07 Blotongan Salatiga with a population of 53 adolescents consisting of 28 boys and 25 girls, and was the total sample. This study aims to determine the significance of the relationship between parenting parents and the social interaction of adolescent Grogol cadets RW 07 Blotongan Salatiga and to determine the significance of interpersonal communication relationships with the social interaction of adolescent Grogol cadets RW 07 Blotongan Salatiga. The data collection technique used in this study was a questionnaire (questionnaire). The data analysis technique used in this study is the Contingency Coefficient and Kendall tau-b. The results of this study are that there is a significant relationship between parenting style and social interaction with a correlation coefficient of 0.957 and a significance value of 0.049 <0.05 and there is also a significant relationship between interpersonal communication and social interaction with the findings of the correlation coefficient. of 0.562* * and a significance value of 0.000 <0.01.